Oxygen Supplementation to Stabilize Preterm Infants in the Fetal to Neonatal Transition: No Satisfactory Answer - Torres-Cuevas, Isabel; Cernada, Maria; Nuñez, Antonio; Escobar, Javier; Kuligowski, Julia; Chafer-Pericas, Consuelo; Vento, Maximo (Frontiers in Pediatrics, 2016)
Fetal life elapses in a relatively low oxygen environment. Immediately after birth with the initiation of breathing the lung expands and oxygen availability to tissue rises by twofold generating a physiologic oxidative stress. However, both lung anatomy and function and the antioxidant defense system do not mature until late in gestation and therefore very preterm infants often need respiratory support and oxygen supplementation in the delivery room to achieve postnatal stabilization. Notably, interventions in the first minutes of life can have long-lasting consequences. Recent trials have aimed to assess what initial inspiratory fraction of oxygen and what oxygen targets during this transitional period are best for extremely preterm infants based on the available nomogram. However, oxygen saturation nomogram informs only of term and late preterm infants but not on extremely preterm infants. Therefore, the solution to this conundrum may still have to wait before a satisfactory answer is available.